Strategic Management Accounting and Data-Driven Innovation For Operational Efficiency In The Southern Border Manufacturing Industry Of Thailand - Raksudjarit, Sukrita; Namburi , Nantharat; Pongkrapan , Nattharawee; Dueloh, Norseeun (International Journal of Accounting and Economics Studies, 2025)
The domestic economy is experiencing continued improvement, driven by the recovery of the tourism sector. In turn, this has led to increased demand for related industrial goods. Businesses must adapt through innovation to survive in a rapidly changing market. Consequently, they are actively seeking competitive advantages to improve operational efficiency. Strategic management accounting is, therefore, a key factor in organizational success, designed to assist in controlling and managing issues related to the economic sector and organizational performance. Furthermore, the development of innovation will enhance operational efficiency and sustain competitiveness. This research aims to analyze the levels of strategic management accounting (SMA), innovation development, and operational performance efficacy within the southern border manufacturing industry of Thailand. This study employs a mixed-methods research design, incorporating structural equation modeling (SEM). The population comprises 136 southern border manufacturing industries. Data collection involves questionnaires and semi-structured interviews. Data analysis utilizes descriptive statistics, structural equation modeling, and content analysis. The research findings indicate that the manufacturing industry exhibits a high level of agreement regarding strategic management accounting, innovation development, and operational efficiency overall. Furthermore, innovation development positively influences operational efficiency, innovation development positively influences strategic management accounting, and strategic management accounting positively influences operational efficiency. Consequently, businesses can utilize these findings as a decision-making guide for employing management accounting techniques and fostering innovation, thereby maximizing resource utilization and leveraging existing knowledge for management to achieve a competitive advantage, ultimately leading to improved operational efficiency.